2018
DOI: 10.35808/ersj/996
|View full text |Cite
|
Sign up to set email alerts
|

Status and Contemporary Development of Employee Inventions Ownership in G-20 Countries

Abstract: The study discusses the ownership arrangements of employee invention in patent law system in several countries that become the members of G-20 and comparable with employee invention arrangement in patent law in Indonesia. The research approach used by normative juridical and the data used is secondary data and used qualitative analysis. The concept of setting a clear ownership of employee inventions by relying on the doctrine hired to invent or shop rights in the adoption of the patent law system in the advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…This can be interpreted as the commitment of the state through the Act, as in Article 3 regarding the objectives, namely to create a conducive business climate through a fair business competition arrangement so as to ensure the certainty of equal business opportunities for large business actors, medium business actors and small business actors. With this exception, the law respects the conditions and efforts of the sustainable small businesses and cooperatives that dominate our national business actors (Roisah et al, 2018;Pangestu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This can be interpreted as the commitment of the state through the Act, as in Article 3 regarding the objectives, namely to create a conducive business climate through a fair business competition arrangement so as to ensure the certainty of equal business opportunities for large business actors, medium business actors and small business actors. With this exception, the law respects the conditions and efforts of the sustainable small businesses and cooperatives that dominate our national business actors (Roisah et al, 2018;Pangestu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The findings also showed that in comparison, in general, in settling tax disputes through the judiciary, there are appeal and cassation efforts in some countries, for example, the United States, the Netherlands, Canada, South Korea, Japan, Malaysia (Pratt & Kulsrud, 2011;Ispriyarso & Saadah, 2019;Roisah et al, 2020). Settlement of tax disputes through judicial institutions in various countries such as the United States (Lederman, 2014), Canada (Arnold, 2019), South Korea (Yun, 2003), Japan (Nakayama, 2007), and Malaysia (Kasipillai, 2000) shows that there are efforts to appeal and cassation.…”
Section: Reform Of Legislative Aspectmentioning
confidence: 94%
“…30 of 1999 concerning Arbitration and ADR are often used by parties in dispute resolution in general, but for the resolution of endowment disputes it still needs to be tested, whether the law can be used as a guideline or not, given the act of endowment has characteristics. 16 The characteristics of endowment acts are the responsibility of endowment property is intended for the community and endowment property must not be lost, damaged, but preserved for the benefit of eternity. If there is a change in objectives and benefits, it must be licensed by PPAIW and BWI as an institution responsible for endowment acts in Indonesia.…”
Section: Resolution Of Endowment Disputesmentioning
confidence: 99%